Cardiovascular risk in the Asia-Pacific region from a nutrition and metabolic point of view: Lipid - Tienboon P. (2014)
Hypercholesterolemia, especially low-density lipoprotein cholesterol, is well-known as a risk factor for coronary heart disease. The prevalence of hyperlipidemia in the Asia-Pacific regions, although not as high as in the North American and European regions, in adults and children varied from country to country. The 'Cardiovascular Risk Factor of Chiang Mai children (CARFACC)' study has shown the small 'n' and capital 'N' phenomenons, where in some individuals, blood lipid levels were tracked from childhood to adulthood. The new concept of programming by early nutrition on later adult health has now been accepted. The prevention of dyslipidemia during childhood should receive more attention.